EP893 Malignant bowel obstruction in gynaecological oncology: are there alternatives to surgery or palliation following failed conservative management?. (1st November 2019) - Korompelis, P; Bennett, D; Rundle, S; Adishesh, M; Kucukmetin, A; Naik, R; O'Donnell, R
Abstract : Introduction/Background: Bowel obstruction (BO) is an infrequent but challenging complication of gynaecological cancer. Management may be surgical, medical or conservative, but there is a lack evidence-based guidance to inform best practice. This study aimed to review BO management in patients with gynaecological malignancy. Methodology: In this retrospective study all patients admitted to the NGOC with radiological evidence of BO (2012–2017) were identified. Patient demographics, clinicopathological data and management details were collated. Outcomes were stratified by management (conservative/Gastrograffin®/stent/surgery). Results: Of the 82 patients included 62(79%) had ovarian cancer. 67(82%) presented with small BO and 15(18%) with large BO. 13(16%) underwent first-line emergency surgery. All remaining patients were initially managed conservatively with a 32% resolution rate. Following failed conservative management, an algorithm utilising level of obstruction and presence of transition point(s) was used to determine subsequent management. In the 43 patients for whom conservative management failed, 11 underwent a trial of Gastrograffin®, 5 underwent endoscopic stenting and 26 underwent emergency surgery. The overall rate of resolution using Gastrograffin® was 64%, for stenting was 80% and for surgical diversion was 100%. 5 patients who were not suitable for surgical intervention were palliated. There were no adverse events from stents or Gastrograffin®. Overall 66(80%) patients were discharged from hospital and 27(40%) received further chemotherapy. In those successfully treated, the median additional survival was 12.4 months (4.2–90.5). Additional survival was greatest in the subgroup with a single distal transition point treated surgically and lowest in the subgroups with multiple or no transition points. Conclusion: Patients with BO are highly heterogenous and should be stratified into treatment pathways based upon radiological assessment of transition point(s). Non-surgical interventions have high rates of success when used in a highly selected subgroup of patients. Survival following management of BO is highly variable which is likely to be a reflection of disease distribution. Disclosure: Nothing to disclose.